PEMODELAN BERBASIS UJI NON-DESTRUKTIF DAN SEMI-DESTRUKTIF YANG DIVALIDASI FREKUENSI ALAMI PADA ASESMEN RELIABILITAS PONDASI JIB CRANE - Heri Khoeri; Naufal Rafif Rizqullah; Badaruddin Badaruddin; Haryo Koco Buwono (RENOVASI : Rekayasa Dan Inovasi Teknik Sipil, 2023)
To ensure the safety of operating the Jib crane, regular inspections and evaluations need to be conducted, including on the foundation structure system. The allowable load specified by the manufacturer only applies when the crane is positioned relatively flat against its support; thus, if the crane is tilted due to settlement at the support during operation, the allowable load will drastically decrease and may cause an overturning. This study was conducted to assess the reliability of the current foundation system after 10 years operation. The foundation system of the Jib crane under investigation consists of steel pipe piles connected to a pile cap at the top and reinforced with bracing between the pipes. Inspections were carried out using non-destructive and semi-destructive testing to obtain actual dimensions and quality of the structural elements. All test data were compiled to serve as input for structural modeling. To ensure the validity of the model, verification was performed with vibration test results. The determination of the number of points and types of tests affects the validity of the model, where the more numerous and comprehensive the tests, the more accurately the model represents actual conditions. The analysis results of the model produced a natural frequency of 1.48 Hz, while the dynamic load test result was 1.5 Hz, with closely matching frequencies indicating sufficiently valid input data, resulting in dynamic structural responses close to reality. The analysis results of the model indicate that the Jib crane foundation is still reliable with a safety factor of 3.1. However, to slow down the corrosion rate of the steel, protective measures are necessary, including periodic painting of the surface of the steel pipe foundation and its supporting bracing, injection into cracked concrete, and protecting concrete from alkali-silica reaction by applying corrosion-resistant bituminous-based painting.